BAHAYA DI BALIK KENIKMATAN TERASI - Khusnah, Laila (JURNAL BIOSHELL, 2012)
Indonesian people are not only familiar with terasi, but also enjoy its made products. Terasi is the product of processing fish or shrimp by giving salt & fermentation in the form of solid paste with a unique smell and taste. In Jember, it can be made of rebon shrimp (Mysis), citrus shrimp (Metapenaeus ensis), and reket shrimp (Atya sp.) with the general traditional methods. Terasi actually has a good nutrient, but it gives bad effects on the structure and function of liver. It’s proven by the result of the research on mouse (Mus musculus) Galur Balb-c with the treatment of giving two kinds of terasi.